A criminalidade de colarinho branco e a necessária investigação contemporânea a partir do Brasil: uma (re)leitura do discurso da impunidade quanto aos delitos do “Andar de Cima” - Beck, Francis Rafael (Universidade do Vale do Rio dos Sinos, 2013)
Of a colony without greater importance, Brazil has become one of the protagonists on new world scenario. Now it’s necessary that this evolution reaches the Criminal Law, supported in 1988 Constitution. However, it’s necessary to give constitutional text a transforming function, with emphasis on the pursuit of achieving a Leadind (and Compromissory) Constitution, passing through discussions around neoconstitutionalism, until reaching Contemporary Constitutionalism. The change from an authoritarian government to a democracy requires a review of the whole repressive system, especially the criminal legal, without disregard the necessary reflections concerning the globalization, risk, society and criminal law expansion influences, not yet sufficiently understood. With regard to white collar crimes, there is great polemics concerning its definition, by switching subjectives (which take into account the agent characteristics), objectives (based on modus operandi) and mixed currents. The idea that the powerful ones receive a benevolent treatment by the criminal justice is so frequent that the task of justify it is much more complex than it might seem view, being including contradicted by some recent analyzes. For the investigation carried out this thesis were used as a parameter six categories of crimes with greater identification with respect to white collar crimes: crimes against the national financial system, the tax system crimes, crimes against the economy, bidding crimes, crimes against the social security and money laundering. Regarding the process of primary criminalization, it was observed that the entrapment average on the white collar crimes investigated (41.93 months) is 61% higher than the property without violence or serious threat (25.94 months) crimes average, moving away a myth spread by common sense. Besides, criminal legislation produced after 1988, intentionally or not, makes a criminal legal normative consolidation of the Federal Constitution content, especially with respect to the supraindividual legal assets linked to white collars, either by the number of laws created or modified, either by the penalties provided. In the same way, legislative projects in relation to the theme have the same tendency to puniteve increase. Regarding the secondary criminalization process, gain special prominence COAF, which centralizes all communications, including those previously forwarded to other agencies (Central Bank, CVM, SUSEP and PREVIC). The operations performed by the Federal Police in relation to the white collar crimes, increased 1,500% between 2003 and 2010. However, between 2006 and 2012, the number of police inquiries initiated by the agency was reduced by 60%. The Public Prosecution Service does not have unified information about complaints offered. Regarding the Brazilian Judiciary, between the years 2000 and 2012, not only white collar crimes not only white collar crimes gave rise to a higher number of decisions in the surveyed courts, as well as resulted in a very large number of condemnatory decisions, far higher than acquittals and extinction of criminal liability. The criminal enforcement, however, continues with the profile of young prisoners, browns, with low education level, and that commit (mostly) crimes against property.
Keywords: Constitucionalização do direito penal; Criminalidade de colarinho branco; Direito penal econômico; Direito penal contemporâneo; Estatísticas penais; Criminal law constitutionalization; White-collar criminality; Economic criminal law; Contemporary criminal law; Criminal statistics; ACCNPQ::Ciências Sociais Aplicadas::Direito